Related factors of serum uric acid in patients with primary hypertension and hyperhomocysteinemia. (2nd April 2016) - Wang, Bei; Lin, Ling; Zhao, Chang
ABSTRACT: Objective : To investigate the related factors of serum uric acid in patients with primary hypertension and hyperhomocysteinemia. Methods : One hundred and ten patients with primary hypertension and hyperhomocysteinemia (homocysteine levels >10 μmol/L) were enrolled into this study, ages from 18 years to 75 years. They were divided into the normal serum uric acid group which contained 74 cases patients (41 cases of male and 33 cases of female) and the hyperuricemia group which contained 36 cases patients (20 cases of male and 16 cases of female). Plasma concentrations of homocysteine, serum uric acid, serum folic acid, blood sugar, triglyceride, total cholesterol, serum low density lipoprotein cholesterol, serum high density lipoprotein cholesterol, blood urea nitrogen, and creatinine were detected in these patients, and the deference of them between the two groups was compared. And then the risk factors of serum uric acid with univariate analysis and multivariate analysis by logistic regression analysis were analyzed. Results : The result of multivariate analysis showed that the incidence of serum uric acid in patients with primary hypertension and hyperhomocysteinemia had significant relationships with systolic blood pressure (OR [odds ratio]: 1.132, 95%CI [confidence interval]: 1.003 1.290, p = 0.043), diastolic blood pressure (OR: 1.353 95%CI: 1.023 1.789, p = 0.034, homocysteine (OR: 1.264, 95%CI: 1.016 1.573, p = 0.035), triglyceride (OR: 9.726, 95%CI: 1.288 73.466, p = 0.027), and creatinine (OR: 1.031, 95%CI: 1.005 1.508, p = 0.018). Conclusion : The indices of systolic blood pressure, diastolic blood pressure, homocysteine, triglyceride, and creatinine were important risk factors of serum uric acid in patients with primary hypertension and hyperhomocysteinemia. It is of great significance to measure multiple risk factors in patients with primary hypertension and hyperhomocysteinemia.